De-colonising the right to housing, one new city at a time: Seeing housing development from Palestine/Israel. (June 2022) - Haas, Oded
The right to housing is generally understood as a local struggle against the global commodification of housing. While useful for recognising overarching urbanisation processes, such understanding risks washing over the distinctive politics that produce the housing crisis and its ostensible solutions in different contexts around the globe. Situated in a settler-colonial context, this paper bridges recent comparative urban studies with Indigenous narratives of urbanisation, to re-think housing crisis solutions from the point of view of the colonised. Based on in-depth interviews with Palestinian citizens of Israel, the paper compares two cases of state-initiated, privatised housing developments, one in Israel and one in the Occupied Palestinian Territories: the new cities Tantour and Rawabi. Each case is examined as a singularity, distinctive formations of the spatialities of Zionist settlement in Palestine, which are now being transformed through privatised housing development. The paper presents these developments as mutually constituted through a colonial-settler project and Palestinian sumud resistance, the praxis of remaining on the land. The paper utilises comparison as a strategy, exploring each new city in turn, to reveal the range of directions in sumud . Thus, by seeing housing development as site for negotiating de-colonisation on the ground, the paper contributes to recent debates over the power of comparative urbanism to re-think global phenomena through treating urban terrains as singularities.